2018
DOI: 10.1002/ijgo.12480
|View full text |Cite
|
Sign up to set email alerts
|

The value of endocervical curettage during loop electrosurgical excision procedures in predicting persistent/recurrent preinvasive cervical disease

Abstract: Positive findings from ECC performed during LEEP were a better predictor of persistent/recurrent disease than margin status, after adjusting the individual variable effect in the Cox modelling. The performance of ECC is recommended during any LEEP performed for CIN2+; in particular, it should never be omitted if endocervical disease is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…Such endocervical sampling right after LEEP was associated with higher predictive value 16 . Similarly, Cuello et al 17 . put forward that ECC results also served as an independent factor in predicting persistent/recurrent diseases, primarily when high‐grade lesions existed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such endocervical sampling right after LEEP was associated with higher predictive value 16 . Similarly, Cuello et al 17 . put forward that ECC results also served as an independent factor in predicting persistent/recurrent diseases, primarily when high‐grade lesions existed.…”
Section: Discussionmentioning
confidence: 95%
“…Such endocervical sampling right after LEEP was associated with higher predictive value. 16 Similarly, Cuello et al 17 put forward that ECC results also served as an independent factor in predicting persistent/recurrent diseases, primarily when highgrade lesions existed. In contrast, Cui et al 6 suggested that both top-hat and ECC procedures provided little prognostic insight in a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that the overall residual disease/recurrence rate at 24 months following surgery was 9.5%, which was consistent with previous reports. The risk factors for persistence/recurrence include age over 45 years, positive resection margins, abnormal intraoperative ECC, persistent postoperative HR-HPV infection, abnormal cytology, and positive ECC following surgery [ 11 , 22 , 23 ]. Intraoperative ECC is generally recognized as indicative of the status of the endocervical margin.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that 31% of cases of recurrent/residual disease were diagnosed using ECC during the follow-up period following a LEEP [ 10 ]. There was another study which recognized ECC during LEEP surgery as an indicator of insider status, found that intraoperative ECC was one of the risk factors of post-LEEP recurrent/residual [ 11 ]. However, few studies reported the relationship between preoperative ECC and recurrent/residual HSIL after LEEP.…”
Section: Introductionmentioning
confidence: 99%
“…ECC is an effective pathological examination method that has attracted increasing attention in recent years. Cuello et al [ 33 ] believe that ECC has irreplaceable value in the diagnosis of cervical lesions. In addition, a positive ECC result is a predictor of persistent/recurrent disease after LEEP treatment.…”
Section: Discussionmentioning
confidence: 99%